Representasi Aktor pada Kasus Penembakan Brigadir Joshua dalam Perspektif Analisis Wacana Theo Van Leeweun - Siti Nur Fatimah; Bambang Yulianto; Heny Subandiyah (LP. Ma'arif Janggan Magetan, 2023)
This study aims to (1) describe the exclusion process in the shooting of Brigadier Joshua, (2) describe the inclusion process in the shooting of Brigadier Joshua. Criminal news is used as an object of research in the field of language, especially discourse analysis. Theo Van Leeweun's discourse analysis model introduces the way a person (actor) is marginalized in a discourse. This research is limited to Deddy Corbuzier's Youtube podcast video discussing the shooting case of Brigadier Joshua. The results of this study found two exclusion processes, namely passivation and nominalization, while the five inclusion processes include differentiation-differentiation, objectivation-abstraction, nomination-categorization, nomination-identification, and determination-indetermination. So it can be concluded that in this video podcast, the actor is marginalized by exclusion because of the actor's relationship involved in the Brigadier Joshua shooting case. While inclusionary marginalization is carried out to maintain the good name of government agencies that are known to be clean and care for the community.